Geomorfologi daerah Tanjung Keramat dan sekitarnya, Kota Gorontalo, Provinsi Gorontalo - Umar, Risky; Arifin, Yayu Indriati; Marina, Siti (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the geomorphological characteristics of the Hulonthalangi area and the Tanjung Keramat Coast in Gorontalo City, which serve as part of the supporting region of the Gorontalo Geopark. The study encompasses variations in topography, slope gradients, river flow patterns and stages, as well as the classification of geomorphological units. In general, the study area is classified into four main morphometric types: Lowland, Inland Lowland, Low Hills, and Hills. Slope analysis indicates variations ranging from flat to steep zones, reflecting differences in slope stability and highlighting areas with high erosion potential. Analysis of river flow patterns shows a dominance of parallel patterns, with valleys shaped like a “V” in the youthful stage and a “U” in the mature stage. Geomorphological characteristics were identified through remote sensing analysis using SRTM DEM data processed with ArcGIS software, and subsequently verified through direct field observations for geomorphological mapping and lithological distribution. This procedure was carried out according to scientific standards to integrate image analysis results with field data. The geomorphological units identified in the study area include Intrusive Hills, Volcanic Hills, Denudational Hills, and Alluvial Plains. Each unit possesses distinctive lithological and topographical characteristics that influence land-use patterns and environmental stability. This study provides significant contributions by supplying geomorphological data that can serve as a reference for planning, development, and sustainable environmental management in the Tanjung Keramat coastal area. The results also support efforts to mitigate potential environmental risks and promote wiser land-use practices in the Hulonthalangi area and Tanjung Keramat Coast.